Causes of Private Tutoring in English: Perspectives of Saudi Secondary School Students and Their Parents - Ghazi N. Alotaibi (International Conference on Education and Language (ICEL), 2014)
The current study examined and described the views of secondary school students and their parents on the causes of private tutoring in English. These views were obtained through two group interviews with the students and parents separately. Several causes were brought up during the two interviews. These causes included difficulty of the English language, weak teacher performance, the need to pass exams with high marks, lack of parents’ follow-up of student school performance, social pressure, variability in student comprehension levels at school, weak English foundation in previous school years, repeated student absence from school, large classes, as well as English teachers’ heavy teaching loads. The study started with a description of the EFL educational system in Saudi Arabia and concluded with recommendations for the improvement of the school learning environment.